The genetic variations and relationship of Madura tobacco (Nicotiana tabacum L.) based on molecular characteristics - Fitri Nadifah; Budi Setiadi Daryono (Indonesian Journal of Biotechnology, 2016)
Madura has at least 22 genotypes of local tobaccos (Nicotiana tabacum L.). This diversity could potentially produce new genotype of tobaccos with superior characters. However, information of the genetic diversity of Madura tobaccos is still limited. The aim of this study was to determine the genetic variation and relationship of 24 genotypes of Madura tobaccos with Random Amplified Polymorphic DNA (RAPD) analysis. In this research we were used 6 single primers for amplification: (OPA-18, OPB-12, OPB-14, OPC-1, OPC-8 and OPC-19) and 2 mixture primers ((OPB-12+OPC-8) and (OPC-1+OPC-19)). Genetic similarity and clustering was analyzed with Unweighted Pair Group Method Arithmetic (UPGMA) method with Numerical Taxonomy and Multivariate Analysis System (NTSYS) version 2.10 software. From this research we found that OPA18425, OPB12450, OPC8500, (OPC19+OPC1)550 and OPC8800 can be used as specific markers. Polymorphic bands percentage with mixture primers was relatively equal with single primers (<60%). The dendogram showed that Madura tobacco genotypes consist of 2 main clusters: cluster A (22 genotypes) and cluster B (2 genotypes: Bukabu Sa’ang and Prancak-95). Madura tobaccos had high genetic similarity between genotypes ranging from 0.80-1.00.